The inverse of the function f(x) = 4(x-3)² + 2 is ![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
The given function is:
f(x) = 4(x - 3)² + 2
To find the inverse of the function:
Make x as the subject of the formula
![4(x-3)^2 = f(x) - 2\\(x-3)^2 = \frac{f(x)-2}{4} \\x - 3 = \sqrt{\frac{f(x)-2}{4} } \\x = \sqrt{\frac{f(x)-2}{4} } + 3](https://tex.z-dn.net/?f=4%28x-3%29%5E2%20%3D%20f%28x%29%20-%202%5C%5C%28x-3%29%5E2%20%3D%20%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%5C%5Cx%20-%203%20%3D%20%5Csqrt%7B%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%7D%20%5C%5Cx%20%3D%20%5Csqrt%7B%5Cfrac%7Bf%28x%29-2%7D%7B4%7D%20%7D%20%2B%203)
Replace x by
and replace f(x) by x
![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
Therefore, the inverse of the function is:
![f^{-1}(x) = \sqrt{\frac{x-2}{4} } + 3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20%5Csqrt%7B%5Cfrac%7Bx-2%7D%7B4%7D%20%7D%20%2B%203)
Learn more here: brainly.com/question/17285960
X^2 + y^2 - 2x + 8y - 47 = 0
x^2 + y^2 - 2x + 8y = 47
(x^2 - 2x) + (y^2 + 8y) = 47
(x^2 - 2(1)x) + (y^2 + 2(4)y) = 47
(x^2 - 2(1)x + 1^2) + (y^2 + 2(4)y + 4^2) = 47 + 1^2 + 4^2
(x - 1)^2 + (y + 4)^2 = 64 = 8^2
r=8
Answer:
The SI unit for length is the meter (abbreviated m); its definition has also changed over time to become more accurate and precise. The meter was first defined in 1791 as 1/10,000,000 of the distance from the equator to the North Pole.
Answer:
We can use quadratic formula
a=3, b= -1, c=4
Step-by-step explanation:
Answer:
That would be option C.
Step-by-step explanation:
I literally just took the quiz and got it right.